CORPORATION CRIME LIABILITY OF PERSPECTIVE PENAL REFORM - Siku, Abdul Salam (Journal of Humanity, 2013)
The setting of the responsibility criminal against corporations in Indonesia starting from the inception of the emergency law number 7 of 1955 on Economic Crime, then followed by some of the last act is Act No. 8 of 2010 on prevention and eradication of the crime of money laundering. In the framework of the renewal of national criminal law and the draft law on The Criminal law (Criminal Code) systematically have set the criminal liability of corporations, whether incorporated corporation law and Corporation who is not a legal entity. Although there have been laws governing corporate crime responsibility about but are still have problems in its application. It can be seen from the lack of a corporate criminal sentenced by the Court.